Near-Infrared Spectroscopy Intravascular Ultrasound Imaging: State of the Art - Kuku, Kayode O.; Singh, Manavotam; Ozaki, Yuichi; Dan, Kazuhiro; Chezar-Azerrad, Chava; Waksman, Ron; Garcia-Garcia, Hector M. (Frontiers in Cardiovascular Medicine, 2020)
Acute coronary syndromes (ACS) secondary to coronary vessel plaques represent a major cause of cardiovascular morbidity and mortality worldwide. Advancements in imaging technology over the last 3 decades have continuously enabled the study of coronary plaques via invasive imaging methods like intravascular ultrasound and optical coherence tomography. The introduction of near-infrared spectroscopy (NIRS) as a modality that could detect the lipid (cholesterol) content of atherosclerotic plaques in the early nineties, opened the potential of studying “vulnerable” or rupture-prone coronary plaques in ACS patients. Intracoronary NIRS imaging offers a unique method of coronary plaque characterization and could become a valuable clinical management tool.